Functional Evaluation of the Virtual Batik and Mask Museum Application using Test Scenario Based - Ibrahim, Fajar Maulana; Astuti, Ika Asti (SISTEMASI, 2026)
The development of digital technology has created new opportunities to introduce and preserve local culture through interactive media, one of which is virtual museums. This study develops a 3D virtual museum application aimed at introducing and preserving batik and mask cultural heritage in response to the need for technology-based educational media. The functionality of the application was evaluated using a scenario-based testing method involving 10 main test scenarios. The testing results indicate an overall excellent performance, with a success rate of 85%. Four activities—including 3D object interaction (mask), wall collider functionality, background sound, and lighting—achieved very good performance. The main weakness was identified in the notification trigger feature, where four users failed to complete the assigned task. The total time required by 10 users was 167.8 seconds, with an average of 16.78 seconds per task. Overall, these results demonstrate that the application has high functional stability and is suitable for use as an innovative and interactive medium for cultural learning.